Um olhar habermasiano acerca do ensino de ciências no 5º ano do ensino fundamental - Costa, Nayara Ferreira (2018)
The studyaimstounderstandthedidacticsof Science Teaching from the thought of Habermas in a class of 5th grade elementaryschoolofthestatepublicnetwork in Manaus. Dividedintothreechapters, thisresearch shows in its first part the theoreticalrelationbetweenHabermasianconceptsandtheteachingofSciencesfrom a democratic perspective. For that, the concepts of emancipation, argumentation, interaction, dialogue and consensus and their interfaces withscienceteachingwerestudied;thischapteralsoanalyzesthe legal andthe curricular basesthatguidetheteachingofSciences. The second stage, presented in chapter two, brings the observation of Science classes and the documentary, epistemological and didactic aspects. However, it wasnoticedthatthe discipline in questionwasmarginalizedsothatthestudentscouldcarry out a training in thesubjectsofPortugueseandMathematicswith a view totheimprovementofindices in a testcalled “ProvaBrasil”. It can be affirmed that the strategic and instrumental interests of the State, materialized in seeking improvement of indexes, overlapped with the right of the student tohave access to a qualityeducation. Thus, Science Teaching in the school reality in question does not allow the student to the construction of an emancipated formation, since the exclusion of this curricular component was carried out in the margins of a public debate, which demonstrates the antidemocratic character with which the school is used. The last chapter refers to the potentialsoftheHabermasianwork for Science Teaching from a didactic sequence carried out in the group whose research was implemented. The analysis of science education through intersubjectively shared interaction and communication has demonstrated the potential of promoting access to culturally socialized scientific knowledge, by enabling the teacher to make corrections and deepen the contents worked during the debates proposed during the classes. Key-words: Didatics; Science Teaching;Epistemology; Habermas.